The Effect Of Competence And Training On Employee Performance Through Job Satisfaction As An Intervening Variable At The Kenangan Coffee Shop In South Tangerang Area - Suryawardhana, Arie Pratomo; Hasanah, Hasanah (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2026)
This study aims to examine and analyze the effect of competence and training on employee performance through job satisfaction as an intervening variable at Kopi Kenangan coffee shops in the South Tangerang area. The independent variables in this study are competence (X1) and job training (X2), the intervening variable is job satisfaction (Z), and the dependent variable is employee performance (Y). Data were collected through the distribution of questionnaires to 50 employees working at various Kopi Kenangan outlets in the South Tangerang region. The research employed a quantitative approach with an associative research design, and data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (SmartPLS). The results show that competence has a positive and significant effect on job satisfaction, with a path coefficient (original sample) of 0.505 and a P-value of 0.000 (< 0.05). Job training also has a positive and significant effect on job satisfaction, with a coefficient of 0.149 and a P-value of 0.043 (< 0.05). Furthermore, competence has a positive and significant effect on employee performance, with a coefficient of 0.182 and a P-value of 0.020 (< 0.05), while job training does not have a significant direct effect on employee performance, with a coefficient of 0.022 and a P-value of 0.829 (> 0.05). Job satisfaction has a positive and significant effect on employee performance, with a coefficient of 0.711 and a P-value of 0.000 (< 0.05). The indirect effect analysis indicates that competence has a significant effect on employee performance through job satisfaction, with a mediation coefficient of 0.359 and a P-value of 0.006 (< 0.05), indicating that job satisfaction acts as a mediating variable. Meanwhile, job training through job satisfaction does not have a significant effect on employee performance, with a mediation coefficient of 0.106 and a P-value of 0.423 (> 0.05), although the indirect effect is greater than the direct effect.